Composite release film as well as preparation method and application thereof
By using a composite structure of cycloolefin resin and LCP mesh in the release film, the deformation and pollution problems of the existing release film under high temperature and tension are solved, and efficient proton exchange membrane preparation and flatness are achieved.
Patent Information
- Application Number
- CN202411386189.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-10
AI Technical Summary
The existing release membranes are prone to deform under high temperature and tension, lack of peeling force and risk of pollution, which affects the flatness and reliability of the proton exchange membrane.
Cycloolefin resin is used as the matrix resin and the LCP mesh is introduced to form a "2+1" three-layer composite structure, which improves mechanical strength and thermal dimensional stability, enhances adhesion, and solves the problem of peeling and separation of the release layer and the substrate .
The film surface flatness under high temperature and tension is achieved, the peeling performance, solvent resistance and temperature resistance are improved, the preparation needs of proton exchange membrane are ensured, and pollution and shedding problems are avoided.
Smart Images

Figure CN119287674A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of film materials, and in particular relates to a composite release film and a preparation method thereof, and further relates to the application of the release film. Background Art
[0002] With the development of hydrogen energy industry, raw materials and preparation process of proton exchange membrane have received much attention. At present, whether it is the homogeneous perfluorosulfonic acid resin membrane made by melt extrusion casting represented by Dupont in the United States, or the porous polytetrafluoroethylene membrane reinforced proton exchange membrane made by solution casting coating represented by Gore in the United States, the release membrane used in the preparation process generally needs to have the following characteristics: 1. Withstand high temperature (150℃-200℃) under large operating tension, keep the membrane surface flat without large deformation; 2. The release membrane and proton exchange membrane have small peeling force, and the peeling process does not affect the flatness of the proton membrane; 3. The release agent layer does not transfer to avoid contaminating the proton exchange membrane.
[0003] Release film, also known as isolation film or peeling film, is a film product that is non-sticky or slightly sticky after contact with specific materials under limited conditions. It is widely used in packaging, printing, transfer, die-cutting and molding. Ordinary release film usually has a double-layer or three-layer structure, that is, PET, PEN, PP or PI film is used as the base layer, and a release agent including fluorine type, silicone type and non-silicone type is coated on one or both sides, and then cured to form a film. In order to meet various special application requirements, various special functional layers or processing methods are adopted, making the release film structure more and more complex and the functions more and more diversified.
[0004] At present, PET and other release film substrates are prone to deformation and stripes under high temperatures above 150°C and tension, which affects the flatness of the proton exchange membrane. Various release agents also have shortcomings. For example, although the release force of the silicone release agent coating is small, it usually causes proton exchange membrane contamination due to silicon transfer; fluorine release agents generally have low surface energy, and the coating slurry is prone to defects such as shrinkage; non-silicon release agents have moderate surface energy and a wide range of release force, but generally have poor temperature resistance and poor adhesion to the substrate. The release layer and the substrate are easy to separate and fall off, affecting the temperature reliability of the release film. Therefore, it is urgent to conduct in-depth research and improvement on release films. Summary of the invention
[0005] The present invention is based on the inventor's discovery and understanding of the following facts and problems: In the related art, CN114603955A discloses a three-layer composite release film for 3D printing process and a preparation method thereof, which respectively adopts poly 4-methyl-1-pentene and long-chain branched modified poly 4-methyl-1-pentene as the surface layer and the middle layer, and the prepared release film has excellent release properties without adding an external release agent, and the film has high light transmittance and good mechanical properties. However, in this scheme, poly 4-methyl-1-pentene and long-chain branched modified poly 4-methyl-1-pentene are used as the main components of the release film, and the tensile strength of the film is usually low, and it is impossible to avoid deformation under the high temperature and tension in the production of proton exchange membranes. CN219634706U discloses a carbon fiber composite release film, including a carbon fiber composite film, the carbon fiber composite film includes a substrate that is a biaxially stretched polyethylene terephthalate base layer, the upper surface of the biaxially stretched polyethylene terephthalate base layer is provided with a silicone oil layer of a multilayer coating, the lower surface of the biaxially stretched polyethylene terephthalate base layer is provided with a woven carbon fiber mesh layer, and the lower surface of the carbon fiber mesh layer is provided with a cast polypropylene layer. The scheme realizes the strength and modulus of the enhanced substrate, thereby improving the composite strength between the film components, making the overall properties of the film more stable, and also improving the tensile strength and toughness, reducing the damage due to scratching and pulling during transportation, and reducing the cost to a certain extent, but the release layer in the technical scheme is a silicone oil layer, there is a risk of silicon transfer and contamination of the proton exchange membrane, and the composite release film includes a silicone oil layer, a PET layer, a carbon fiber net and a polypropylene layer multilayer structure, and there is a curling and warping phenomenon caused by the difference in thermal dimensional change rate at high temperature. Therefore, it is necessary to further improve the release film to meet the preparation requirements of the proton exchange membrane.
[0006] The present invention aims to solve one of the technical problems in the related art to at least a certain extent. To this end, the embodiments of the present invention provide a composite release film and a preparation method thereof. By using COC as a resin matrix and introducing LCP mesh, the release film not only has excellent mechanical strength and thermal dimensional stability, but also solves the problem of separation of the release layer from the substrate. The excellent performance of the composite release film enables it to meet the requirements of the proton exchange membrane preparation process.
[0007] A method for preparing a composite release film according to an embodiment of the present invention comprises the following steps:
[0008] a. Mixing a cycloolefin resin with a molecular weight of 20,000 to 80,000, a chlorinated polyolefin resin and a diluent to obtain a release agent solution;
[0009] b. coating the release agent solution obtained in step a on the substrate film, and then covering it with a layer of LCP mesh cloth;
[0010] c. Continue to coat a layer of the release agent solution of step a on the LCP mesh of step b, and peel off the substrate film after baking to obtain a composite release film.
[0011] The advantages and technical effects brought by the preparation method of the composite release film of the embodiment of the present invention are as follows: 1. In the method of the embodiment of the present invention, a cycloolefin resin with a selected molecular weight is used as the base resin, so that the release film has excellent peeling performance, solvent resistance, temperature resistance and high surface energy. If the molecular weight of the cycloolefin resin is too high, it will be difficult to dissolve completely, resulting in poor film surface quality, thereby reducing the peeling performance. If the molecular weight of the cycloolefin resin is too low, the temperature resistance of the release film will be poor, and the mechanical properties will also be reduced; 2. In the embodiment of the present invention, a cycloolefin resin with better mechanical properties is introduced into the middle of the release film. The LCP mesh serves as a reinforcement layer, which further improves the mechanical strength, rigidity and temperature resistance of the composite release film, and enables the release film to maintain a flat surface without significant deformation under high temperature and tension; 3. In the method of the embodiment of the present invention, the fibers and grids of the LCP mesh are completely wrapped and infiltrated with cycloolefin resin, and the formed composite structure can maximize the adhesion. The release layer has a strong bonding force with the LCP mesh and is not easy to fall off and separate, which effectively solves the problem of the release layer and the substrate falling off and separating in the prior art. The prepared composite release membrane has excellent performance and can meet the preparation requirements of the proton exchange membrane.
[0012] In some embodiments, in step a, the diluent includes at least one of xylene, cyclohexane, tetrahydrofuran or 1,4-dioxane.
[0013] In some embodiments, in step a, the ratio of cycloolefin units to chain olefin units in the cycloolefin resin is 50:50 to 85:15, and the molecular weight is 20,000 to 50,000; the cycloolefin resin has an alkyl side chain with 3 to 10 carbon atoms; the glass transition temperature of the cycloolefin resin is ≥130°C, and the thermal decomposition temperature is ≥400°C.
[0014] In some embodiments, in step a, the chlorinated polyolefin resin includes at least one of chloroacetic acid resin, polyvinyl chloride, polyvinylidene chloride or chlorinated polypropylene; and / or the chlorinated polyolefin resin has a molecular weight of 20,000 to 100,000.
[0015] In some embodiments, in step a, the release agent solution has a solid content of 12-25 wt % and a viscosity of 35-110 mPa·s.
[0016] In some embodiments, in step a, the mass ratio of cycloolefin resin to chlorinated polyolefin resin in the release agent solution is 100:(0.5-6).
[0017] In some embodiments, in step b, the melting temperature of the LCP mesh is ≥280°C; the single filament diameter of the LCP mesh is 24-35 μm, the thickness is 35-50 μm, the mesh opening size is 130-180 μm, and the mesh number is 140-180; the tensile strength of the LCP mesh is ≥160 MPa; the surface of the LCP mesh is treated with corona or plasma, and the surface tension of the LCP mesh is ≥28 mN / m.
[0018] In some embodiments, in step b, the wet thickness of the coating release agent solution is 400 μm to 500 μm.
[0019] In some embodiments, in step c, the wet thickness of the coated release agent solution is 350 μm to 450 μm.
[0020] The embodiment of the present invention also provides a composite release film, which includes a cycloolefin resin layer, an LCP mesh layer and a cycloolefin resin layer in sequence, wherein the molecular weight of the cycloolefin resin in the cycloolefin resin layer is 20,000 to 80,000. The composite release film of the embodiment of the present invention has a "2+1" three-layer composite structure constructed by the cycloolefin resin layer and the LCP mesh, so that the composite release film not only has excellent peeling performance, solvent resistance, temperature resistance, high surface energy, and extremely high mechanical strength and rigidity, but also can keep the film surface flat without large deformation under high temperature and tension. At the same time, the composite structure of the release film of the embodiment of the present invention can maximize the adhesion and solve the problem of separation of the release layer from the substrate. The excellent performance of the composite release membrane of the embodiment of the present invention enables it to meet the preparation requirements of proton exchange membranes.
[0021] In some embodiments, the composite release film is prepared by the method of an embodiment of the present invention.
[0022] The embodiment of the present invention also provides an application of a composite release membrane in preparing a proton exchange membrane. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 Schematic diagram of the structure of the composite release film according to an embodiment of the present invention. DETAILED DESCRIPTION
[0024] Embodiments of the present invention are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and intended to be used to explain the present invention, but should not be understood as limiting the present invention.
[0025] The present invention provides a method for preparing a composite release film, comprising the following steps:
[0026] a. Mixing a cycloolefin resin with a molecular weight of 20,000 to 80,000, a chlorinated polyolefin resin and a diluent to obtain a release agent solution;
[0027] b. coating the release agent solution obtained in step a on the substrate film, and then covering it with a layer of LCP mesh cloth;
[0028] c. Continue to coat a layer of the release agent solution of step a on the LCP mesh of step b, and peel off the substrate film after baking to obtain a composite release film.
[0029] In the preparation method of the composite release film of the embodiment of the present invention, cycloolefin resin is used as the base resin, so that the release film has excellent peeling performance, solvent resistance, temperature resistance and high surface energy. If the molecular weight of the cycloolefin resin is too high, it will be difficult to dissolve completely, resulting in poor film surface quality, thereby reducing the peeling performance. If the molecular weight of the cycloolefin resin is too low, the release film will have poor temperature resistance and also reduce the mechanical properties. In the embodiment of the present invention, LCP mesh with excellent mechanical properties is introduced in the middle of the release film as a reinforcing layer, which further improves the mechanical strength, rigidity and temperature resistance of the composite release film, and enables the release film to keep the film surface flat without large deformation under high temperature and tension. In the method of the embodiment of the present invention, the fibers and grids of the LCP mesh are completely wrapped and infiltrated by the cycloolefin resin, and the formed composite structure can maximize the adhesion. The release layer has a strong bonding force with the LCP mesh and is not easy to fall off and separate, which effectively solves the problem of the release layer and the substrate falling off and separating in the prior art. The prepared composite release membrane has excellent performance and can meet the preparation requirements of the proton exchange membrane.
[0030] In some embodiments, in step a, the diluent includes at least one of xylene, cyclohexane, tetrahydrofuran or 1,4-dioxane. In the embodiment of the present invention, the cycloolefin resin and the chlorinated polyolefin resin are fully dissolved and dispersed in the diluent, preferably, heated and stirred at 50-90° C. for 20-40 minutes, and filtered to obtain a uniformly dispersed release agent solution.
[0031] In some embodiments, in step a, the solid content of the release agent solution is 12-25wt%, and the viscosity is 35-110mPa·s. In the embodiments of the present invention, controlling the solid content of the release agent solution is conducive to forming a uniform cycloolefin resin layer, further improving the comprehensive performance of the composite release film.
[0032] In some embodiments, in step a, the ratio of cycloolefin units to alkene units in the cycloolefin resin (COC resin) is 50:50 to 85:15, and the molecular weight is 20,000 to 50,000; the cycloolefin resin has an alkyl side chain with 3 to 10 carbon atoms; the glass transition temperature of the cycloolefin resin is ≥130° C., and the thermal decomposition temperature is ≥400° C. In the embodiments of the present invention, the use of the preferred COC resin is conducive to further improving the peeling performance, solvent resistance, temperature resistance and surface energy of the composite release film.
[0033] In some embodiments, in step a, the chlorinated polyolefin resin includes at least one of chloroacetic acid resin, polyvinyl chloride, polyvinylidene chloride or chlorinated polypropylene; the molecular weight of the chlorinated polyolefin resin is 20000 to 100000. In the embodiment of the present invention, the introduction of chlorinated polyolefin resin into the matrix resin cycloolefin resin can effectively improve the cohesion and tensile strength of the material and avoid tearing of the release film.
[0034] In some embodiments, in the step a, in some embodiments, in the step a, the mass ratio of the cycloolefin resin to the chlorinated polyolefin resin in the release agent solution is 100:(0.5-6). In the embodiments of the present invention, by controlling the ratio of the cycloolefin resin to the chlorinated polyolefin resin, it is beneficial to further improve the performance of the composite release film. If too much chlorinated polyolefin resin is introduced, the temperature resistance of the release film will be reduced and the peeling force will be greatly increased. If too little chlorinated polyolefin resin is introduced, the improvement of the cohesion and strength of the cycloolefin resin is limited, which is not conducive to the improvement of mechanical properties.
[0035] In some embodiments, in step b, the melting temperature of the LCP mesh is ≥280°C; the single filament diameter of the LCP mesh is 24-35 μm, the thickness is 35-50 μm, the mesh opening size is 130-180 μm, and the mesh number is 140-180; the tensile strength of the LCP mesh is ≥160 MPa.
[0036] In some embodiments, in step b, the surface of the LCP mesh is subjected to corona or plasma treatment, and the surface tension of the LCP mesh is ≥28mN / m. In the embodiment of the present invention, by subjecting the LCP mesh to corona or plasma treatment, the surface of the mesh can be roughened and polar groups can be formed, thereby increasing the surface energy of the mesh and promoting the wettability and adhesion of the cycloolefin resin solution to the mesh.
[0037] In some embodiments, in step b, the wet thickness of the coating release agent solution is 400 μm to 500 μm.
[0038] In some embodiments, in step c, the wet thickness of the coated release agent solution is 350 μm to 450 μm.
[0039] like Figure 1 As shown, an embodiment of the present invention further provides a composite release film, which includes a cycloolefin resin layer, an LCP mesh layer and a cycloolefin resin layer in sequence, wherein the molecular weight of the cycloolefin resin in the cycloolefin resin layer is 20,000 to 80,000. The composite release film of the embodiment of the present invention has a "2+1" three-layer composite structure constructed by the cycloolefin resin layer and the LCP mesh, so that the composite release film not only has excellent peeling performance, solvent resistance, temperature resistance, high surface energy, and extremely high mechanical strength and rigidity, but also can keep the film surface flat without large deformation under high temperature and tension. At the same time, the composite structure of the release film of the embodiment of the present invention can maximize the adhesion and solve the problem of the release layer falling off and separating from the substrate. The excellent performance of the composite release membrane of the embodiment of the present invention enables it to meet the preparation requirements of proton exchange membranes.
[0040] In some embodiments, the composite release film is prepared by the method of an embodiment of the present invention.
[0041] The composite release film of the embodiment of the present invention has a thickness of 80-100 μm, a tensile strength of 100-140 MPa, a water contact angle of 93-100°, a peeling force with the proton exchange membrane of 5 gf-10 gf, and the release coating does not separate or fall off.
[0042] The present invention is described in detail below with reference to embodiments.
[0043] Example 1
[0044] 15 parts by weight of COC resin (molecular weight 50,000), 0.075 parts by weight of polyvinylidene chloride copolymer resin (PVDC, molecular weight 20,000) and 85 parts by weight of diluent (the diluent consists of xylene and tetrahydrofuran in a volume ratio of 1:1) are added to a glass container, stirred until large particles are dissolved, stirred at 80° C. for 30 minutes, filtered with a 500-mesh filter cloth while hot, to obtain a release agent solution having a solid content of 15.1wt%, and a mass ratio of COC resin to chlorinated polyolefin resin of 100:0.5.
[0045] The release agent solution is coated on the substrate film PET with a wet thickness of 400μm, and then quickly covered with a layer of LCP mesh to make it completely soaked and allowed to stand for 3 minutes. The melting temperature of the LCP mesh used is 285℃, the single filament diameter of the LCP mesh is about 30μm, the thickness is 35μm, the mesh opening size is 135μm, the mesh mesh number is 150, and the tensile strength TD of the LCP mesh is 165MPa and MD is 160MPa.
[0046] A 400 μm release agent solution was coated on the upper layer of the LCP mesh, dried at room temperature for 3 minutes, and then placed in an oven at 120° C. for 6 minutes. The PET substrate was peeled off to obtain a composite release film with a thickness of 82 μm.
[0047] Example 2
[0048] 15 parts by weight of COC resin (molecular weight 20,000), 0.075 parts by weight of polyvinylidene chloride copolymer resin (PVDC, molecular weight 50,000) and 85 parts by weight of diluent (the diluent consists of xylene and tetrahydrofuran in a volume ratio of 1:1) are added to a glass container, stirred until large particles are dissolved, stirred at 80° C. for 40 minutes, filtered with a 500-mesh filter cloth while hot, to obtain a release agent solution having a solid content of 15.1wt%, and a mass ratio of COC resin to chlorinated polyolefin resin of 100:0.5.
[0049] The release agent solution is coated on the substrate film PET with a wet thickness of 400 μm, and then quickly covered with a layer of LCP mesh cloth to make it completely soaked and left to stand for 3 minutes. The LCP mesh cloth used in this embodiment is the same as that in Example 1.
[0050] 350 μm release agent solution was coated on the upper layer of the LCP mesh, dried at room temperature for 3 minutes, and then placed in an oven at 120° C. for 6 minutes. The PET substrate was peeled off to obtain a composite release film with a thickness of 80 μm.
[0051] Example 3
[0052] 15 parts by weight of COC resin (molecular weight 20,000), 0.075 parts by weight of polyvinylidene chloride copolymer resin (PVDC, molecular weight 100,000) and 85 parts by weight of diluent (the diluent consists of xylene and tetrahydrofuran in a volume ratio of 1:2) are added to a glass container, stirred until large particles are dissolved, stirred at 80° C. for 40 minutes, filtered with a 500-mesh filter cloth while hot, to obtain a release agent solution having a solid content of 15.1wt%, and a mass ratio of COC resin to chlorinated polyolefin resin of 100:0.5.
[0053] The release agent solution is coated on the substrate film PET with a wet thickness of 400 μm, and then quickly covered with a layer of LCP mesh cloth to make it completely soaked and left to stand for 3 minutes. The LCP mesh cloth used in this embodiment is the same as that in Example 1.
[0054] 350 μm release agent solution was coated on the upper layer of the LCP mesh, dried at room temperature for 3 minutes, and then placed in an oven at 120° C. for 6 minutes. The PET substrate was peeled off to obtain a composite release film with a thickness of 80 μm.
[0055] Example 4
[0056] 15 parts by weight of COC resin (molecular weight 20,000), 0.9 parts by weight of polyvinylidene chloride copolymer resin (PVDC, molecular weight 20,000) and 85 parts by weight of diluent (the diluent consists of xylene and tetrahydrofuran in a volume ratio of 1:1) are added to a glass container, stirred until large particles are dissolved, stirred at 80° C. for 30 minutes, filtered with a 500-mesh filter cloth while hot, to obtain a release agent solution having a solid content of 14.9wt%, and a mass ratio of COC resin to chlorinated polyolefin resin of 100:6.
[0057] The release agent solution is coated on the substrate film PET with a wet thickness of 400 μm, and then quickly covered with a layer of LCP mesh cloth to make it completely soaked and left to stand for 3 minutes. The LCP mesh cloth used in this embodiment is the same as that in Example 1.
[0058] 350 μm release agent solution was coated on the upper layer of the LCP mesh, dried at room temperature for 3 minutes, and then placed in an oven at 120° C. for 6 minutes. The PET substrate was peeled off to obtain a composite release film with a thickness of 80 μm.
[0059] Example 5
[0060] 20 parts by weight of COC resin (molecular weight 50,000), 1.2 parts by weight of polyvinylidene chloride copolymer resin (PVDC, molecular weight 100,000) and 80 parts by weight of diluent (the diluent consists of xylene and tetrahydrofuran in a volume ratio of 1:2) are added to a glass container, stirred until large particles are dissolved, stirred at 80° C. for 30 minutes, filtered with a 500-mesh filter cloth while hot, to obtain a release agent solution having a solid content of about 20.9wt%, and a mass ratio of COC resin to chlorinated polyolefin resin of 100:6.
[0061] The release agent solution is coated on the substrate film PET with a wet thickness of 500 μm, and then quickly covered with a layer of 50 μm thick LCP mesh cloth to make it completely soaked and allowed to stand for 3 minutes. The LCP mesh cloth used in this embodiment is the same as that in Example 1.
[0062] A 450 μm release agent solution was coated on the upper layer of the LCP mesh, dried at room temperature for 3 minutes, and then placed in an oven at 120° C. for 6 minutes. The PET substrate was peeled off to obtain a composite release film with a thickness of 100 μm.
[0063] Comparative Example 1
[0064] The method is the same as that of Example 1, except that the amount of polyvinylidene chloride copolymer resin added is 1.2 parts by weight, that is, the weight ratio of COC resin to chlorinated polyolefin resin is 100:8.
[0065] Comparative Example 2
[0066] The method is the same as that of Example 1, except that the LCP mesh is not added, and the release agent solution is directly coated to obtain a release film with a thickness of 80 μm.
[0067] Comparative Example 3
[0068] The method is the same as that of Example 1, except that the molecular weight of the COC resin is 100,000.
[0069] Comparative Example 4
[0070] The method is the same as that of Example 1, except that the molecular weight of the COC resin is 10,000.
[0071] Comparative Example 5
[0072] The method is the same as that of Example 1, except that the polyvinylidene chloride copolymer resin is not added.
[0073] Comparative Example 6
[0074] The method is the same as that of Example 1, except that the LCP mesh is replaced by a PEEK mesh.
[0075] The composite release films prepared in the embodiments and comparative examples were subjected to performance tests, and the thickness, tensile strength and water contact angle of the release films were measured. The test results are shown in Table 1.
[0076] The method for measuring the thickness of the release film is as follows: refer to the method in GB / T 6672-2001 (Mechanical measurement method for thickness of plastic films and sheets).
[0077] The method for determining the tensile strength of the release film is as follows: refer to the method of GB / T 13022-1991 (Test method for tensile properties of plastic films).
[0078] The method for determining the water contact angle of the release film is as follows: the test is carried out in accordance with the method of GB / T 30693-2014 (Measurement of the contact angle between plastic film and water).
[0079] A composite proton exchange membrane was prepared by coating the composite release membrane of each embodiment and comparative example with a perfluorosulfonic acid resin solution, that is, coating the release membrane with a perfluorosulfonic acid resin and an ePTFE reinforcement layer, and baking the composite release membrane at 80°C for 5 minutes and then at 150°C for 10 minutes. The peeling force between different release membranes and the proton exchange membrane and the adhesion force of the release membrane were measured, and the results are shown in Table 1.
[0080] The method for determining the peeling force between the release film and the proton exchange membrane is as follows: the test is based on the method of GB / T 25256-2010 (Test method for 180° peeling force and residual adhesion rate of release film for optical functional film).
[0081] The method for determining the adhesion of the release layer of the release film is as follows: referring to the method of GB / T 9286-2021 (cross-cut test for paints and varnishes) to determine the shedding ratio of the release layer.
[0082] The method for determining the temperature resistance of the release film is as follows: the release film is treated at 180°C for 20 minutes, and the surface roughness is tested using a surface profiler.
[0083] The test method for the solvent resistance of the release layer of the release film is: referring to the method of GB / T 23989-2009 (Determination of Solvent Resistance of Coatings by Wiping), the resistance of the release layer to solvents (especially water-alcohol mixed solvents) is tested.
[0084] Table 1
[0085]
[0086] It can be seen from Table 1 that the composite release film prepared in the embodiment of the present invention has excellent peeling performance, solvent resistance, temperature resistance, high surface energy, and extremely high mechanical strength and rigidity, and can keep the membrane surface flat without large deformation under high temperature and tension in the preparation of proton exchange membrane. In addition, the composite structure of the release film in the embodiment of the present invention can maximize the adhesion, the cycloolefin resin release layer is tightly combined with the LCP mesh layer, and the cycloolefin resin layer of the release layer is not easy to fall off, which effectively solves the problem of the release layer and the substrate falling off and separating in the prior art.
[0087] In Comparative Example 1, since too much chlorinated polyolefin resin was added to the release agent solution, the chlorinated polyolefin itself had a large peeling force with the proton membrane, and the peeling force between the prepared proton exchange membrane and the release membrane was relatively large.
[0088] In Comparative Example 2, no LCP mesh was introduced as a reinforcing mesh, resulting in a relatively low strength of the cycloolefin release film.
[0089] In Comparative Example 3, the molecular weight of the COC resin used is too high, and particles exist in the solution due to poor solubility, resulting in excessive particles on the surface of the release film, and the peeling force between the prepared proton exchange membrane and the release film is relatively large.
[0090] In Comparative Example 4, the molecular weight of the COC resin used is too low. Due to the low decomposition temperature and glass transition temperature, the temperature resistance of the release film is poor, and the peeling force between the prepared proton exchange membrane and the release film is as high as 29.4 gf. In the adhesion test, the cycloolefin resin layer falls off by 7%.
[0091] In Comparative Example 5, since no chlorinated polyolefin resin was added to the release agent solution and the cohesive force of the COC resin itself was slightly poor, 60% of the cycloolefin resin layer fell off in the adhesion test.
[0092] In Comparative Example 6, the reinforcing mesh used is PEEK mesh. Since the strength of PEEK mesh itself is much lower than that of LCP mesh, the mesh does not sufficiently enhance the strength of the release film, and the strength of the release film is relatively low.
[0093] In the present invention, the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0094] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A method for preparing a composite release film, characterized in that: The steps include: a. Mixing a cycloolefin resin with a molecular weight of 20,000 to 80,000, a chlorinated polyolefin resin and a diluent to obtain a release agent solution; b. coating the release agent solution obtained in step a on the substrate film, and then covering it with a layer of LCP mesh cloth; c. Continue to coat a layer of the release agent solution of step a on the LCP mesh of step b, and peel off the substrate film after baking to obtain a composite release film.
2. The preparation method according to claim 1, characterized in that: In the step a, the diluent includes at least one of xylene, cyclohexane, tetrahydrofuran or 1,4-dioxane.
3. The preparation method according to claim 1, characterized in that: In the step a, the ratio of cycloolefin units to chain olefin units in the cycloolefin resin is 50:50 to 85:15, and the molecular weight is 20,000 to 50,000; and / or the cycloolefin resin has an alkyl side chain with 3 to 10 carbon atoms; and / or the glass transition temperature of the cycloolefin resin is ≥130°C and the thermal decomposition temperature is ≥400°C.
4. The preparation method according to claim 1, characterized in that: In the step a, the chlorinated polyolefin resin includes at least one of chloroacetic acid resin, polyvinyl chloride, polyvinylidene chloride or chlorinated polypropylene; and / or the molecular weight of the chlorinated polyolefin resin is 20,000 to 100,000.
5. The preparation method according to claim 1, characterized in that: In the step a, the release agent solution has a solid content of 12-25 wt % and a viscosity of 35-110 mPa·s; And / or, the mass ratio of the cycloolefin resin to the chlorinated polyolefin resin in the release agent solution is 100:(0.5-6).
6. The preparation method according to claim 1, characterized in that: In the step b, the melting temperature of the LCP mesh is ≥280°C; And / or, the LCP mesh has a single filament diameter of 24-35 μm, a thickness of 35-50 μm, a mesh opening size of 130-180 μm, and a mesh count of 140-180; And / or, the tensile strength of the LCP mesh is ≥160MPa; And / or, the surface of the LCP mesh is treated with corona or plasma, and the surface tension of the LCP mesh is ≥28mN / m.
7. The preparation method according to claim 1, characterized in that: In the step b, the wet thickness of the coating release agent solution is 400 μm to 500 μm; And / or, in the step c, the wet thickness of the coating release agent solution is 350 μm to 450 μm; And / or, in the step c, the baking temperature is 90-150° C. and the baking time is 2-8 min.
8. A composite release film, characterized in that: The invention comprises a cycloolefin resin layer, an LCP mesh layer and a cycloolefin resin layer in sequence, wherein the molecular weight of the cycloolefin resin in the cycloolefin resin layer is 20000-80000.
9. The composite release film according to claim 8, characterized in that: The composite release film is prepared by the method according to any one of claims 1 to 7.
10. Use of the composite release membrane prepared by the method according to any one of claims 1 to 7 or the composite release membrane according to claim 8 or 9 in preparing a proton exchange membrane.
Citation Information
Patent Citations
Carbon fiber composite release film
CN219634706U